1994
DOI: 10.1128/jb.176.8.2227-2234.1994
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal exchange of minor components of type 1 and F1C fimbriae results in hybrid organelles with changed receptor specificities

Abstract: Type 1 and FlC fimbriae are surface organelles of Escherichia coli which mediate receptor-specific binding to different host surfaces. Such fimbriae are found on strains associated with urinary tract infections. The specific receptor binding of the fimbriae is due to the presence of receptor recognition proteins present in the organelles as minor structural elements. The organization of the fim and foc gene clusters encoding these fimbriae, as well as the structures of the organelles, are very similar, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 38 publications
1
43
1
Order By: Relevance
“…The focA gene encodes the major fimbrial subunit, while focG and focH encode minor fimbrial subunits; the focC and focD genes are required to encode a chaperone protein and molecular usher (41). It has been reported previously that the two-component export systems of type 1 and F1C fimbriae are interchangeable and that the minor fimbrial structural elements of these two fimbrial systems can be exchanged, resulting in hybrid organelles with changed receptor specificity (21,22,24). However, the regulatory proteins of the foc operon have remained largely uncharacterized.…”
mentioning
confidence: 99%
“…The focA gene encodes the major fimbrial subunit, while focG and focH encode minor fimbrial subunits; the focC and focD genes are required to encode a chaperone protein and molecular usher (41). It has been reported previously that the two-component export systems of type 1 and F1C fimbriae are interchangeable and that the minor fimbrial structural elements of these two fimbrial systems can be exchanged, resulting in hybrid organelles with changed receptor specificity (21,22,24). However, the regulatory proteins of the foc operon have remained largely uncharacterized.…”
mentioning
confidence: 99%
“…A cluster of eight genes (foc) is necessary for the biogenesis of F1C fimbriae (21,22,40,50,51). The F1C fimbrial complex is composed of the major subunit protein FocA (16 kDa) and the minor subunits FocF (17 kDa), FocG (15 kDa), and FocH (30 kDa) (40).…”
mentioning
confidence: 99%
“…A fundamental question is how the bacteria are able to avoid mixing these up during biosynthesis. We have recently shown that reciprocal exchange of minor components of type 1 and F1C fimbriae results in phenotypically normal hybrid organelles with heterologous receptor specificities (18). The present observations concerning the flexibility of the biogenesis systems provide additional insight into the molecular background of this phenomenon.…”
Section: Discussionmentioning
confidence: 78%
“…Plasmids pPKL4, pPKL63, pPKL34, pPKL84, and pPKL104 containing all or part of the fim gene cluster have been described previously (15-17, 19, 21). Plasmids pPKL143 containing the foc gene cluster has also been described previously (18). Plasmid pPKL161 (fimD) was made by insertion of a HindIII-EagI fragment from plasmid pPKL68 (17) into HindIII-EagI cut pACYC184 (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation